3D melatonin nerve scaffold reduces oxidative stress and inflammation and increases autophagy in peripheral nerve regeneration. Issue 4 (3rd August 2018) - Qian, Yun; Han, Qixin; Zhao, Xiaotian; Song, Jialin; Cheng, Yuan; Fang, Zhiwei; Ouyang, Yuanming; Yuan, Wei‐En; Fan, Cunyi
Abstract: Peripheral nerve defect is a common and severe kind of injury in traumatic accidents. Melatonin can improve peripheral nerve recovery by inhibiting oxidative stress and inflammation after traumatic insults. In addition, it triggers autophagy pathways to increase regenerated nerve proliferation and to reduce apoptosis. In this study, we fabricated a melatonin‐controlled‐release scaffold to cure long‐range nerve defects for the first time. 3D manufacture of melatonin/polycaprolactone nerve guide conduit increased Schwann cell proliferation and neural expression in vitro and promoted functional, electrophysiological and morphological nerve regeneration in vivo. Melatonin nerve guide conduit ameliorated immune milieu by reducing oxidative stress, inflammation and mitochondrial dysfunction. In addition, it activated autophagy to restore ideal microenvironment, to provide energy for nerves and to reduce nerve cell apoptosis, thus facilitating nerve debris clearance and neural proliferation. This innovative scaffold will have huge significance in the nerve engineering.